(3GdJcedI hGdEJeGe dcJGH GdJYQja hGdEYdGes - (3eMeO Hf Ydj Hf GdNVQ GdZSGfi GdeYQha HGHf YScQs; (3GdSgjdj , YHO GdQMef Hf YHO Gddg Hf CMeO Hf GUHZ GdNKYej CHh GdbGSe, CHh GdbGSe,J (B581 (3g` s ((3eMeO Hf YeQ GdHRGR s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eJee GdfYe hGdEMSGf heYde GdMce ddEfSGf GdN s
(3BNQgG (B:s
(3hGbJUQJ Ydi PcQ GdCbhGd ai GdCcKQ ef ZjQ ESfGO LQkG Ydi ePgH GdTjN ai cJGHg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B42 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs